the Obstacles Encountering Practicing Handball From The Players’ Perspectives In The Clubs Of The West Bank- Palestine. - hamdane ahmed, youcef; abou zahra nidhal, abed el nacer; al asaad mourad, riadh (sports creativity, 2025)
The obstacles encountering practicing handball from the players’ perspectives in the clubs of the West Bank- Palestine. Abstract: This study aims to acknowledge the obstacles that face practicing handball from the points of view of the West Bank clubs’ players. A descriptive and scanning method has been used through designing a questionnaire which includes 35 paragraphs concerning obstacles, distributed over the following five fields: the field of motivation, the field of financial ability, media and social field, the technical field (trainers and referees) and the administrative field (club and union). The sample included 103 players from the West Bank’s clubs who practice handball. The results indicated that obstacles are due to the increase in turnout at doing other sports like football in comparison with handball, lack of closed halls with international standards, having no culture of the game in the Palestinian environment, lack of courses that raise the training-level of handballtrainers, and no financial motivation system that suits the achievements of the players and clubs. The first-ranked field regarding the obstacles encountering the practice of handball game is the financial possibilities field. The second is the administrative field (club and union). The third is the motivation field. The fourth is the media and social field. The fifth is the technical field in (trainers and referees). According to the aforementioned results, the recommendations are: 1_ The necessity to support this game financially. 2_ Providing material motivation and help to the players solve their problems. 3_ Working to provide suitable places and training tools to practice this game. 4_ Disseminating and acknowledging the culture of this game by media, via teaching the importance of this game by schools, universities and sports institutions in order to raise the incentive to play this game. 5_ Working hard to qualify and raise the position of the referees and trainers via holding courses and workshops. 6- Having an administrative and leading body which is capable of managing, organizing, supervising and solving the problems that face the players and the trainers.